Efficacy of combination therapy of Hyaluronic acid and Methylprednisolon verses Hyaluronic acid single therapy in knee Osteoarthritis : A comparative study (Northern International Medical College Journal, 2020)
Background: Osteoarthritis of knee joint is one of the most common problem which cause pain, loss of function even joint disability and increases misery and morbidity in old age. Now a day’s intra-articular injection of single Hyaluronic acid or corticosteroids (Methylprednisolone) are using for knee osteoarthritis cases. But the combined therapy by injection of both Hyaluronic acid and Methyl prednisolone are not so much practiced and still under debate.Objectives: To compare the efficacy of intra-articular injection of combined Hyaluronic acid and Methyl prednisolone with single Hyaluronic acid alone.Methods: A prospective, comparative study was done in Northern International Medical College Hospital, Dhaka, during May 2017 to April 2018 at Out Patient Department with 80 patients (132 knees). Patients were randomized into two groups: Group-A with 40 patients with 15 unilateral and 25 bilateral knee cases (65 knees) were treated with combined Hyaluronic acid and Methyl prednisolone and Group-B with 40 patients with13 unilateral and 27 bilateral knee cases (67 knees) were infiltrated with single Hyaluronic acid. Results were evaluated with Knee Society Score (KSS) and Visual analogue score (VAS) at the 1st week, 1st month and 3rd month after injection.Result: In both Group (A and B) patients of age 61–70 years were highest, 50% and 45% respectively. Male and female ratio was 1:2.2. At the 1st week KSS for pain in Group-A (mean 65.6) was better than Group-B (mean 57.4). At the 1st month mean pain scores (Group-A 72.4, Group-B 64.4) and the 3rd month (Group-A 81.4, Group-B 75.6) and mean function scores at 1st week (Group-A 61.3, Group-B 49.6)), 1st month (Group-A65.1, Group-B 53.6) and 3rd month (Group-A68.4, Group-B 59.4). The KSS for pain and function improved in combination therapy group.VAS decreased in both groups.Conclusion: As combination therapy by Hyaluronic acid and Methyl prednisolone showed better efficacy than single Hyaluronic acid. Therefore, combination of these two drugs in a single vial can be used as an effective and easy nonoperative treatment of knee osteoarthritis.Northern International Medical College Journal Vol.10 (2) Jan 2019: 366-369